CITRA PEREMPUAN DALAM MASYARAKAT HINDU (KAJIAN TEKSTUAL SASTRA HINDU) - Geriya, S.Swarsi (Jurnal Studi Jender SRIKANDI; Vol. 6, No. 2 Juli 2007)
The immage of Hinduism woman is a description of an excellent and interesting woman. According to Hindu?s literature, the immage of Hindu?s woman especially in Balinese society have several characteristics such as: a) they are very religious realized in their role and activity in the sacred ceremony; b) they have a work ethic and honesty also loyalty which is reflected in the story of Dewi Kausalya (the wife of King Dasarata) or Sri Rama?s mother; and c) They have no maintain the truth/Dharma. The description above is the characteristic of ideal women properly still exist in this modern period.Meanwhile, in the real life there are so many things already changed, such as the change of moral value and chalenge life. It causes the gap between religion literature and the reality applied; therefore mostly found the insulting of woman.
Keywords: immage, woman, Hinduism